To Compare the Outcome of Estrogen and Betamethasone Cream in the Treatment of Labial Adhesion in Pre-pubertal Girls (Bangladesh Journal of Child Health, 2020)
Background: Labial adhesion is a condition of prepubertal girls where the labia are fused over the vaginal opening and/or urethra.Objective: The purpose of the study was to compare the outcome of estrogen and betamethasone cream in the treatment of labial adhesion.Materials and methods: This prospective comparative study was conducted among 100 pre-pubertal girls with labial adhesion where at least 50% vaginal opening was fused. Patients previously treated with estrogen or betamethasone for labial adhesion was excluded from the study. Fifty patients were treated with betamethasone cream (group 1) and fifty patients with estrogen cream (group 2) after randomization. All patients were followed at 3rd week, 6th week, 3rd month, 6th month and then release of adhesion and adverse effects were noted.Results: Within 3 weeks no adhesion was found in 84.0% participants in group 1 and 64.0% participants in group 2, which showed significant statistical differences (p=0.023). Within 6 months recurrence of adhesion was found in 2.2% participants in group 1 and 23.4% in group 2, which also showed highly significant statistical differences (p=0.004). Success rate was 90.0% and 72.0% within 6 months in group 1 and in group 2 respectively and the difference was statistically significant (p=0.022).Conclusion: Betamethasone cream appears to be a superior agent in terms of effectiveness, safety and cost than estrogen cream in the treatment of labial adhesion in pre-pubertal girls.Bangladesh J Child Health 2019; VOL 43 (3) :161-164